Pengembangan Video Pembelajaran IPS Dengan Materi Masalah Sosial Untuk Siswa Kelas V Sekolah Dasar - Hajizah, Nurul; Guslinda, Guslinda; Noviana, Eddy (CV. Rayyan Dwi Bharata, 2025)
This study aims to see how social problems occur in grade V elementary school students with video-based learning media. The research method uses the (RD) Research and Development method with the ADDIE approach. The subject of this study is a grade V student of State Elementary School 024 Tarai Bangun Tambang District, Kampar Regency. Data collection used a questionnaire that was distributed to 29 students in class V . The results of the study showed that the feasibility data of video media showed an average score of 90% with a very valid category. The second aspect of assessment, the language aspect, obtained an average score of 80% with a very valid category. The third aspect is the media aspect, which has an average score of 86.36% with a very valid category. From these three aspects, the average final score of the validation assessment was obtained by showing a score of 88.41% with a very valid category. The results of the research from the learning media can be seen as follows: the validation of material experts got a score of 90%, the validation of linguists 88%, the validation of media experts 86.36%, the validation of practitioners I got a percentage score of 90.83%, the validation of ptactification II 100%, the one-on-one trial got a score of 88.33%, and the small group trial got a percentage score of 86.12%. Thus, it can be concluded that the application of learning video media is very feasible to improve the way students learn actively.